2020
DOI: 10.1163/21971927-bja10004
|View full text |Cite
|
Sign up to set email alerts
|

Corporate-startup Co-creation for Increased Innovation and Societal Change

Abstract: The emphasis on corporate-startup collaboration has reached a new level in the context of digital transformation of most industries. Co-creation, as one non-equity based model for corporate-startup collaboration is increasingly getting attention among corporations and startups, but also among local governments. However, even if companies, governments, and startups invest in this approach for innovation and societal change, the concept is under-researched. The purpose of this paper is to further examine corpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Several different models for corporate-startup collaboration have been identified. Based on a several years long research study, Steiber & Alänge (2020) identified and described eight models for corporatestartup collaboration: 1. Acquisition, 2.…”
Section: Models For Corporate-startup Collaborationmentioning
confidence: 99%
See 4 more Smart Citations
“…Several different models for corporate-startup collaboration have been identified. Based on a several years long research study, Steiber & Alänge (2020) identified and described eight models for corporatestartup collaboration: 1. Acquisition, 2.…”
Section: Models For Corporate-startup Collaborationmentioning
confidence: 99%
“…Platform,6. Corporate Startup Program, The different models will be described below in accordance to the findings from Steiber & Alänge (2020).…”
Section: Models For Corporate-startup Collaborationmentioning
confidence: 99%
See 3 more Smart Citations